A call to action becomes practice: cardiac and vascular surgery during the COVID-19 pandemic based on the Lombardy emergency guidelines. (25th June 2020) - Bonalumi, Giorgia; Giambuzzi, Ilaria; Barbone, Alessandro; Ranieri, Camilla; Cavallotti, Laura; Trabattoni, Piero; Naliato, Moreno; Polvani, Gianluca; Torracca, Lucia; Pelenghi, Stefano; Ragni, Franco; Russo, Claudio Francesco; et al.
Abstract: OBJECTIVES: During the Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) pandemic, Northern Italy had to completely reorganize its hospital activity. In Lombardy, the hub-and-spoke system was introduced to guarantee emergency and urgent cardiovascular surgery, whereas most hospitals were dedicated to patients with coronavirus disease 2019 (COVID-19). The aim of this study was to analyse the results of the hub-and-spoke organization system. METHODS: Centro Cardiologico Monzino (Monzino) became one of the four hubs for cardiovascular surgery, with a total of eight spokes. SARS-CoV-2 screening became mandatory for all patients. New flow charts were designed to allow separated pathways based on infection status. A reorganization of spaces guaranteed COVID-19-free and COVID-19-dedicated areas. Patients were also classified into groups according to their pathological and clinical status: emergency, urgent and non-deferrable (ND). RESULTS: A total of 70 patients were referred to the Monzino hub-and-spoke network. We performed 41 operations, 28 (68.3%) of which were emergency/urgent and 13 of which were ND. The screening allowed the identification of COVID-19 (three patients, 7.3%) and non-COVID-19 patients (38 patients, 92.7%). The newly designed and shared protocols guaranteed that the cardiac patients would be divided into emergency, urgent and ND groups. The involvement of the telematic management heart team allowed constant updates and clinical discussions. CONCLUSIONS: The hub-and-spoke organization system efficiently safeguards access to heart and vascular surgical services for patients who require ND, urgent and emergency treatment. Further reorganization will be needed at the end of this pandemic when elective cases will again be scheduled, with a daily increase in the number of operations.